2017
DOI: 10.4103/aam.aam_213_16
|View full text |Cite
|
Sign up to set email alerts
|

Burden of informal caregivers of stroke survivors: Validation of the Zarit burden interview in an African population

Abstract: Background:Informal care giving can be burdensome particularly where the option of institutionalized informal care scarcely exist.Objective:To look at the burden of informal caregivers of stroke survivors using the Zarit burden interview (ZBI).Method:64 stroke survivors were assessed for demographics of age, gender, duration of follow-up since discharged from in-patient care, modified Rankin score at the time of discharge and at the time of evaluation for this study and the most important informal care giver a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 20 publications
3
14
1
Order By: Relevance
“…The mean age of CGs in this study was 42.8 (±12.6) years, which is in keeping with other studies reviewed. [4611] Majority of CGs were female, married spouses of SSs also in agreement with other studies reviewed. [4671823] These findings are not unusual because, in most African communities, family CG roles are mostly ascribed to female spouses.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The mean age of CGs in this study was 42.8 (±12.6) years, which is in keeping with other studies reviewed. [4611] Majority of CGs were female, married spouses of SSs also in agreement with other studies reviewed. [4671823] These findings are not unusual because, in most African communities, family CG roles are mostly ascribed to female spouses.…”
Section: Discussionsupporting
confidence: 88%
“…Caregiver burden refers to alterations in CGs emotional and physical health which can occur when care demands outweigh available resources,[10] the extent to which CGs feels there emotional, physical, social life, and financial status has suffered as a result of caregiving,[11] which indeed affects their overall health and quality of life (QoL). [12] Caregiver burden has been shown to have cumulative negative effects on SSs treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they are prone to bear care burden. [ 29 , 30 ] In this study, only 31.6% of the caregivers had no burden or light burden, and 68.4% of the caregivers had moderate burden and above, indicating that care stress of stroke caregivers are ubiquitous. [ 31 ] Literature review showed that the risk of anxiety and depression increased by 60% to 70% with each 1 unit increase of the caregiver burden.…”
Section: Discussionmentioning
confidence: 79%
“…The SPB may threaten individuals' coping and continued progress following stroke. Most studies, however, focused on the burden of caregivers of stroke survivors ( 11 ) or were cross-sectional studies ( 8 – 10 ). Despite existing evidence that SPB experienced by stroke patients affects stroke rehabilitation, emotional and mental health, and QOL, studies on the SPB of patients in the acute and recovery phase shortly after stroke are inadequate.…”
Section: Introductionmentioning
confidence: 99%